A European answer to the Chinese question in Africa? The global gateway and European-Chinese competition in Africa - Mah, L.; Haastrup, T.; Duggan, N. (ECPR 12th Biennial Conference of the SGEU, 2024)
On 1 December 2021 the European Union (EU) launched the Global Gateway (GG). This new 300-billion EUR European strategy is intended to boost the EU's involvement in areas such as transport infrastructure, green energy, and digitalisation in developing countries. The African continent is expected to benefit with half of the expected figures. Much of the debate in the past few years has attempted to dissect the (geo)political, financial and economic dimensions of the GG from the perspective of Brussels and EU Member States´ policymakers. However, very little has been discussed on how African policymakers have perceived the GG. This paper will thus focus on how African agency within regional bodies there understanding of the GG within the framework of Africa-EU relations. Moreover, it will compare this agency with that which has been displayed in the past decade of relations between Africa and China. Drawing on an ontological security analytical framework, the paper seeks to understand the new dynamics and contestations of African agency in the continent´s relations with the EU and China that have been ignored in both mainstream and critical approaches to EU foreign policy studies.